Solidarity & survival : an oral history of Iowa labor in the twentieth century - Stromquist, Shelton, 1943- (Iowa City, IA : University of Iowa Press, 1993)
In Solidarity and Survival, three generations of Iowa workers tell of their unrelenting efforts to create a labor movement in the coal mines and on the rails, in packinghouses and farm equipment plants, on construction sites and in hospital wards. Drawing on nearly one thousand interviews collected over more than a decade by oral historians working for the Iowa Federation of Labor, AFL-CIO, Shelton Stromquist presents the resonant voices of the men and women who defined a new, prominent place for themselves in the lives of their communities and in the politics of their state.
Introduction -- Origins and Traditions: The Making of an Iowa Labor Movement -- Conditions of Work Before the Union -- Rebuilding the House of Labor in the 1930's -- Work and War: Securing the Union -- Promise and Perils of the Postwar Era -- The World of the Shopfloor in the 1950's -- Coming to Terms: Gender, Race, and the New Solidarity -- Politics and the Renewal of the Labor Movement -- Epilogue -- Appendix: Interviewees in the Iowa Labor History Oral Project -- Index
Includes bibliographical references (pages 12-18) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Labor movement -- Iowa -- History -- 20th century; Labor unions -- Iowa -- History -- 20th century; Mouvement ouvrier -- Iowa -- Histoire -- 20e siècle.; Syndicats -- Iowa -- Histoire -- 20e siècle.; BUSINESS & ECONOMICS -- Labor; POLITICAL SCIENCE -- Labor & Industrial Relations; Labor movement; Labor unions; Iowa; 1900-1999; History